Symmetry Breaking in the Lowest-Lying Excited-State of CCl4: Valence Shell Spectroscopy in the 5.0–10.8 eV Photon Energy Range - Luiz V. S. Dalagnol; Sarvesh Kumar; Alessandra S. Barbosa; Umma S. Akther; Nykola C. Jones; Søren V. Hoffmann; Márcio H. F. Bettega; Paulo Limão-Vieira (Molecules)
We report absolute high-resolution vacuum ultraviolet (VUV) photoabsorption cross-sections of carbon tetrachloride (CCl4) in the photon energy range 5.0–10.8 eV (248–115 nm). The molecular spectrum and electronic structure have been comprehensively investigated together with quantum chemical calculations, providing geometries, bond lengths, vertical excitation energies and oscillator strengths. The major electronic excitations have been assigned to valence and Rydberg transitions which are also accompanied by vibrational excitation assigned to degenerate stretching, <semantics><msubsup>v3′</msubsup><mfenced separators="|">t2</mfenced></semantics> and degenerate deformation <semantics><msubsup>v4′</msubsup><mfenced separators="|">t2</mfenced></semantics> modes. The rather complex nuclear dynamics along the degenerate deformation mode, <semantics><msubsup>v4′</msubsup><mfenced separators="|">t2</mfenced></semantics>, have been thoroughly investigated by Time-Dependent Density Functional Theory (TD-DFT) method. The relevant Jahn–Teller distortion operative within the lowest-lying electronic excited-state is shown here for the first time in order to yield a weak absorption feature at 6.156 eV. Further calculations on the potential energy curves for the singlet excited-states along the C–Cl stretching coordinate show the relevance of efficient C–Cl bond excision.